2017
DOI: 10.1039/c7ta01113j
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid lithium-ion capacitors with asymmetric graphene electrodes

Abstract: A dual-graphene LIC delivered a high energy density of 222 W h kg−1 with a power density of 410 W kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…The Li metal electrode and the Batteries 2018, 4, 4 6 of 39 negative electrode are electronically isolated from each other and the negative electrode is charged with a low current or electrical shorting in order to perform lithiation. This process can be repeated for several charge/discharge cycles, for a defined period of time or until the electrode reaches a defined potential [30,34,53,54]. However, the electrochemical pre-lithiation process often requires a re-assembling step of the pre-lithiated negative electrode into the LIB cell, which increases the expenditure and reduces the possibility to use this method in a commercial way.…”
Section: Concepts For Electrochemical Pre-lithiationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Li metal electrode and the Batteries 2018, 4, 4 6 of 39 negative electrode are electronically isolated from each other and the negative electrode is charged with a low current or electrical shorting in order to perform lithiation. This process can be repeated for several charge/discharge cycles, for a defined period of time or until the electrode reaches a defined potential [30,34,53,54]. However, the electrochemical pre-lithiation process often requires a re-assembling step of the pre-lithiated negative electrode into the LIB cell, which increases the expenditure and reduces the possibility to use this method in a commercial way.…”
Section: Concepts For Electrochemical Pre-lithiationmentioning
confidence: 99%
“…All techniques and methods described above can be applied for the pre-lithiation of LICs, such as the electrochemical pre-lithiation [54,157,160,161], the pre-lithiation with additives inside the negative or positive electrode [162][163][164] or the pre-lithiation through direct contact with Li metal [165,166]. In contrast to pre-lithiation of LIBs, pre-lithiated LICs are already commercially available as described in the followings section.…”
Section: Pre-lithiation In Lithium-ion Capacitorsmentioning
confidence: 99%
“…Previous investigations on the reduced graphene oxides (rGO) have demonstrated that introducing extra spacers is an effective way to reduce this restacking. For example, Tang and co‐workers developed a single‐wall carbon nanotube and graphene (SG) composite to reduce restacking of the graphene nanosheets . As in the case of ACs, heteroatom doping can effectively improve the electrochemical performance of graphene‐based cathode by enhancing the conductivity and providing pseudocapacitive active sites.…”
Section: Materials For Sodium‐ion Capacitorsmentioning
confidence: 99%
“…For example, Sun et al [54] prepared a single-wall carbon nanotube (SWCNT) and graphene composite (SG). For example, Sun et al [54] prepared a single-wall carbon nanotube (SWCNT) and graphene composite (SG).…”
Section: Graphenementioning
confidence: 99%